Gender equality, intersectionality and diversity in Europe - Agustín, Lise Rolandsen (Palgrave Macmillan, 2013)
Analyzing the developments which have characterized EU gender equality policies and women's transnational activism since the introduction of multiple discrimination policies in the 1990s, this book identifies two interrelated challenges: diversity of women's interests, and degendering of policies. Drawing on discursive policy analysis, it addresses the interaction between policies, institutions and civil society actors in relation to gender equality, diversity and intersectionality at the European level. Rolandsen Agust̕n successfully integrates the concepts of diversity and gender equality into a contextualized approach to analyzing transnational intersectionality. This unique approach focuses on processes of institutionalization and mobilization, which are addressed in relation to the institutional setup of the EU, its policies and policymaking structures, as well as transnational civil society mobilization and interaction with EU institutions